ANOTASI ATAS REGULASI PERLINDUNGAN DATA PRIBADI DI INDONESIA (Jurnal Magister Hukum Perspektif, 2021)
The Industrial Revolution Concept 4.0 agree that personal data is economic value data. Personal data can be used for commercial purposes, so clear and specific arrangements need to be made. In Indonesia, the meaning of this type of personal data has not yet reached the highest level of Laws up to Government Regulations. This study aims to analyze the regulations on private data or data that are personal in Indonesia and make comparisons with several countries in Europe that implement personal data protection agreements. In this series of studies, the method used is a normative juridical method which consists of three types relating to statutory regulations, conceptual approaches, and comparative approaches. Based on the results of the study, a common thread related to the regulation of data privacy protection legislation No. 19 of 2016 concerning ITE up to the latest namely Permenkominfo No. 20 of 2016. However, at the technical level, regulations and regulations regarding the use of personal data in Indonesia are still at the point of legal vacuum. This can be seen in several sectors when considering the provisions in force in the European Union (GDPR) such as the meaning and type of Personal Data, standardization of Company Regulations, and provisions related to notifications that have supported personal data. The conclusion that can be drawn is that the substance of norms in GDPR is a norm that is more accommodating to the needs of people in Indonesia, because it is a guarantee of the availability of much better personal data. In addition, the deletion of personal data on request is also done more effectively and efficiently. Keywords: Regulation, Protection, Deletion, Personal Data.